Development and Validation of a Nomogram for Predicting the Risk of Bell's Stage II/III Necrotizing Enterocolitis in Neonates Compared to Bell's Stage I - Song, Shuting; Zhang, Jian; Zhao, Yuwei; Dai, Liying (Frontiers in Pediatrics, 2022)
Background: Early prediction and early diagnosis of Necrotizing Enterocolitis (NEC) are important for clinical management of NEC. The main objective of this study was to construct a nomogram model predicting the risk of neonatal NEC. Patients and Methods: A total of 730 NEC newborns diagnosed from January 2015 to January 2021 were retrospectively studied. They were randomly divided into training and validation groups in the ratio of 7:3. A nomogram model for predicting NEC was developed based on all independent risk factors by multivariate regression analysis. The model's performance was evaluated mainly through three aspects: the area under the curve (AUC) to verify discrimination, Hosmer-Lemeshow test and calibration curves to validate consistency, and the decision curve analysis (DCA) check clinical effectiveness. Results: Predictors contained in the prediction model included gestational age (GA), birth weight(BW), asphyxia, septicemia, hypoglycemia, patent ductus arteriosus (PDA). The nomogram model containing the above-mentioned six risk factors had good discrimination ability in both groups, and the AUC was 0.853 (95%CI, 0.82-0.89) and 0.846 (95% CI, 0.79-0.90), respectively. The calibration curve and DCA confirmed that the nomogram had a good consistency and clinical usefulness. Conclusions: This individual prediction nomogram based on GA, BW, asphyxia, septicemia, hypoglycemia, PDA is a useful tool to predict NEC, which can help neonatologists identify NEC early and take some effective measures. Keywords: Necrotizing enterocolitis, neonate, nomogram, risk factors, prediction model